Pašvērtēšanas metode 3.klasē. - Uršte, Renāte (Latvijas Universitāte, 2006)
The paper consists of 49 pages, 1 chart and 5 graphs. There enclosed 4 appendixes. The objective of paper is theoretically analyse improving approaches of sense of rhythm and repose on acquired results in experimental work recommend methods and approaches for sense of rhythm improving of young learners. For compleating this objective there were used several tasks: 1.Theoretically analyse theoretical approaches of improving of sense of rhythm. 2.To analyse the peculiarities of pupils in primary school 3.To check up the developed methods and efficiency of approaches in experimental work and analyse acquired results for improving a sense of rhythm. Qualification paper consists of two parts – theoretical and practical researching part. In theoretical part are researched different theoretical approaches, summarized Latvian music pedagogues and composers methodical recommendations, analysed methods and approaches for developing rhythm of pupils in primary school, researched and characterised young learners peculiarities as well as persetive peculariaties of music for young learners. In practical part – research of sense of rhythm and development, which is realized in Music lessons after worked out experimental programme.

Authoress Renate Urste diploma work ‘’Self estimation method in third grade’’ the point is to analyse self-estimations methods meaning in education and to make recommendations to self-estimations methods in class. Diploma work includes: •features estimation and self-estimation functions in primary education •there has been analysed the younger pupils physical character •there has been analysed the self-estimations meaning in pupils ‘’Me’’ conceptions making •to base on my personal competence there was made methodical manners and guidance for third grades pupils self-estimation Self-estimation methods are the way to pupils’ competence building in self learning discovery process, building liability in education process. However this is a chance for pedagogues to see Childs upgrowth, to systemise pupils’ skills and performance, to get information about pupils’ interests, needs and abilities. This reflexive leash promotes positive relationships with parent, pupils and teachers.
Self-assessment method in Grade 3.
Keywords: Pedagoģija